PENGARUH PENGGUNAAN MEDIA COMIC BOOK PADA PEMBELAJARAN BAHASA ARAB BAGI MAHASISWA FAKULTAS ILMU PENDIDIKAN UNIVERSITAS KH. A. WAHAB HASBULLAH JOMBANG - Nurul Hidayah; Sujono - (Al-Lahjah, 2019)
Arabic is a foreign language that is widely studied by students, especially in the field of Islamic education. However, for some students who have never known being something new it even becomes something that is difficult to learn. To overcome this, researchers created a learning medium in the form of comic books to facilitate students' understanding of Arabic. The methodology used by researchers is R&D (Research and Development). Using this method, researchers designed a product in the form of a comic book, then made a product, and the final step was to evaluate the product to the validation stage. The results obtained from these studies are in the form of influence on learning, reading interest and Arabic language abilities of students. Keywords: media, comic book, learning.